The Contribution of Oil Palm Plantations to Farmers’ Household Income - Nita Oktavia; Ine Fausayana; La Ode Kasno Arif (International Journal of Technology and Education Research, 2026)
This research was conducted in Aopa Village, Angata District, South Konawe Regency. The aim was to determine the income of oil palm farmers and the contribution of oil palm plantation businesses to their household income. The population in this study consisted of 24 oil palm farmers, all of whom were sampled using the census method. The data used consisted of primary and secondary data obtained through interviews, observation, documentation, and literature review. Data analysis was conducted descriptively and quantitatively using income analysis and contribution analysis. The results showed that the average income of oil palm farming farmers in Aopa Village was IDR 20,598,520 per hectare per year or IDR 1,716,544 per month. Meanwhile, the average total income of farmer households reached IDR 33,765,187 per year, derived from oil palm farming, non-oil palm farming, and non-agricultural income. The contribution of oil palm farming income to total household income was 61%, making it a significant contributor